University Mergers in Lithuania: A Media Discourse Analysis - Bružienė, Rūta (Acta Paedagogica Vilnensia, 2019)
University mergers could be perceived as a political process – at least during the first stages of the process, which contain discussions about common visions, goals, and measures. Therefore, a university merger could be analyzed using the methods of political discourse analysis, which allows to understand how public discourses about merging universities have been constructed, legitimized, and institutionalized. It is important to understand the process of university mergers as a political phenomenon that is constructed by stakeholders using public discourses. Public discourses, reflected in the media, form the society’s opinion about a university merger and have influence on policy decisions and the implementation process of these decisions. In this context, the purpose of this article is to analyze the written content related to university merger issues published in online media during the course of three years (2016–2018). Quantitative content analysis was made using software Hamlet II 3.0. Some trends of public discourse related to university mergers have been detected. It is noticed that a university merger is primarily related to the improvement of higher education quality and the needs of business and the state in public discourse. However, the declared political goal of seeking competitiveness and quality of research is not developed and reflected in the media. This shows a certain fragmentation of ideas in the process of merging universities, because the society, the academic community, and the government agree (as reflected in the documents (2017)) that only a unity of research and studies could assure the highest quality university education and international recognition. Also, differences between business and university mergers have been noticed. More rational arguments are used to justify business mergers than social and cultural ones (Vaara, Tienari 2002) when compared to university mergers. Stakeholders usually use a combination of social and rational arguments in public discourse to justify university mergers.